The effect of the faults to the tectono-stratigraphy evolution in the Panyu low uplift - Liang, Yuanyuan; Yang, Dongsheng; Chen, Shi; Zhang, Gongcheng; Bai, Zhizhao; Liang, Xinxin; Wang, Yunuo; Wang, Long; Guo, Shuai; Ji, Mo; Yan, Hui (Frontiers in Earth Science, 2024)
The Panyu low uplift is located in the middle of the Central Uplift Belt of the PRMB, which has experienced multiple episodes of tectonic movements since the Cenozoic, and the faults are extensively developed there. The fault activities had a significant influence on the migration and accumulation of oil and gas, as well as the sedimentation. In order to recognize the effect of the faults on the tectono-straigraphy evolution in the uplift, based on the high-resolution seismic and latest drilling well data, the study has comprehensively analyzed the geometry and kinematics of these faults, as well as the sedimentary filling evolution of the residual depressions. The results show that two major fault systems has developed in the uplift: the deep and shallow fault systems. The former was dominated by a series of NEE and NW-trending high-angle listric/plane faults, along with several low-angle detachment normal faults, which were under the joint control of the NW-SE and NS-trending extensional stress during the Eocene. The latter was dominated by NW-NWW trending strike-slip normal faults with tension-shear properties under the NEE trending dextral strike-slip stress field in the late Miocene. The uplift had undergone five tectonic evolution stages: the initial rifting stage (Tg-T83), the intensive rifting stage (T83-T80), the rifting and depression transitional stage (T80-T70), the thermal subsidence depression stage (T70-T35), and the tectonic reactivation stage (T35-T10). Based on the 3D seismic phase interpretation and drilling sample analyses, the study shows that during the initial rifting stage, the Panyu low uplift manifested as multistage depositional center. The sedimentary strata were distributed in the downthrown wall of the depression-controlling faults, exhibiting multiple subsidence and sedimentary centers, and the depressions was supplied by multi-provenance systems. During the intense rifting period, the depression widened, the lacustrine basins were connected with each other, and the sedimentary center migrated. During the rifting and depression transitional stage, the faults controlling on deposition weakened. The thick Enping formation from the northwest provenance direction is unconformably overlaid on the uplift. Meanwhile, various types of sedimentary facies were developed in the residual depressions, including delta, semi-deep lacustrine, shallow lacustrine, and shore-shallow lacustrine deposits.